Do Trade and Poverty Cause Each Other? Evidence from BRICS. (January 2022) - Rahman, Mohd Nayyer; Rahman, Nida; Turay, Abdul; Hassan, Munir
Any two variables that are observable have one or the other form of relationship. This is particularly a statistical relationship. But for a statistical relationship to be cause and effect, a theoretical relationship is important. The theoretical relationship can be quantified to search for the evidence of causality. The possible outcomes can be no causality, unidirectional causality, or bidirectional causality. The present study aims at searching for evidence from BRICS countries regarding trade causing poverty or vice versa. Applied econometrics approach is used in the study. Panel econometric techniques have been employed to identify presence/absence of causality between the variables. Apart from this, the study also uses equality of means to identify whether trade and poverty proxies are symmetrical or asymmetrical. The study finds no causal relationship between trade and poverty for BRICS countries except that poverty headcount at 3.2 per day causes trade balance. With respect to the impact on the GINI index, lowest 10 percent income share and poverty headcount ratios are integral to reduce the inequality in the BRICS countries.